Colorectal cancer surveillance in Hodgkin lymphoma survivors at increased risk of therapy-related colorectal cancer: Study design - Rigter, L.; Spaander, M.; Moons, L.; Bisseling, T.; Aleman, B.; de Boer, J.; Lugtenburg, P.; Janus, C.; Petersen, E.; Roesink, J.; Raemaekers, J.; van der Maazen, R.; et al. (2017)
Background: Second primary malignancies are a major cause of excess morbidity and mortality in cancer survivors. Hodgkin lymphoma survivors who were treated with infradiaphragmatic radiotherapy and/or high-dose procarbazine have an increased risk to develop colorectal cancer. Colonoscopy surveillance plays an important role in colorectal cancer prevention by removal of the precursor lesions (adenomas) and early detection of cancer, resulting in improved survival rates. Therefore, Hodgkin lymphoma survivors treated with infradiaphragmatic radiotherapy and/or high-dose procarbazine could benefit from colonoscopy, or other surveillance modalities, which are expected to reduce colorectal cancer incidence and mortality. Current knowledge on clinicopathological and molecular characteristics of therapy-related colorectal cancer is limited. The pathogenesis of such colorectal cancers might be different from the pathogenesis in the general population and therefore these patients might require a different clinical approach. We designed a study with the primary aim to assess the diagnostic yield of a first surveillance colonoscopy among Hodgkin lymphoma survivors at increased risk of colorectal cancer and to compare these results with different screening modalities in the general population. Secondary aims include assessment of the test characteristics of stool tests and evaluation of burden, acceptance and satisfaction of CRC surveillance through two questionnaires. Methods/Design: This prospective multicenter cohort study will include Hodgkin lymphoma survivors who survived =8years after treatment with infradiaphragmatic radiotherapy and/or procarbazine (planned inclusion of 259 participants). Study procedures will consist of a surveillance colonoscopy with removal of precursor lesions (adenomas) and 6-8 normal colonic tissue biopsies, a fecal immunochemical test and a stool DNA test. All neoplastic lesions encountered will be classified using relevant histomorphological, immunohistochemical and molecular analyses in order to obtain more insight into colorectal carcinogenesis in Hodgkin lymphoma survivors. The Miscan-model will be used for cost-effectiveness analyses. Discussion: Evaluation of the diagnostic performance, patient acceptance and burden of colorectal cancer surveillance is necessary for future implementation of an individualized colorectal cancer surveillance program for Hodgkin lymphoma survivors. In addition, more insight into treatment-induced colorectal carcinogenesis will provide the first step towards prevention and personalized treatment. This information may be extrapolated to other groups of cancer survivors. Trial registration: Registered at the Dutch Trial Registry (NTR): NTR4961.